Digital Image Storage System and Human Body Data Matching Algorithm for Medical Aesthetic Application - CHA JENNIFER; CHEN CHUN-LEON (2012)
A human body data matching algorithm for medical aesthetic application includes the step of providing a human body image acquisition unit, the step of using the human body image acquisition unit to obtain a digital 3D image data of the body of a person during an optimal lifetime of the person, the step of storing the digital 3D image data in a data storage bank, the step of fetching the digital 3D image data from the data storage bank when going to perform a medical aesthetic surgery, and the step of e) matching the digital 3D image data for reference in the medical aesthetic surgery to avoid communication errors between the patient and the surgeon.